Preparation and physicochemical properties: a new extruded rice using cassava starch and broken rice flour - Xia, Wen; Lin, Yanyun; Wang, Fei; Liu, Yunfei; Liu, Rui Hai (Frontiers in Sustainable Food Systems, 2024)
With the increasing demand for nutrition and health, many researchers are trying to develop a rice product with lower aging rate and convenient nutrient fortification.Being composed of high amylopectin content, cassava starch (CS) shows a lower retrogradation tendency compared to rice starch. So, it has a broad application prospect to partially replace rice starch with CS in rice by extrusion technology. In this study, a new extruded rice (ER) was prepared by broken rice flour and CS using single-screw extruder through "improved extrusion cooking technology", and the maximum addition level of CS in ER was 30%. Color parameters and texture profile analysis showed that ER was a little darker in appearance with lower hardness, adhesiveness and chewiness. Rapid visco analysis demonstrated that the viscosity of ER paste appeared earlier during the initial heating phase and displayed a lower retrogradation trend than normal rice in the cooling process. The gelatinization temperature and gelatinization enthalpy decreased with the increasing CS in ER, while the degree of gelatinization increased to 76.36% when the content of CS was 30% after extrusion. The X-ray diffraction patterns of control was typical A-type structure, while ER changed to V-type structure with a lower degree of crystallinity.The microstructure observation showed that ER exhibited a looser and more porous structure with increasing the content of CS, which facilitated easier cooking and nutritional enhancement.